Learning cleanroom microfabrication operations in virtual reality – An immersive and guided learning experience - Fang Wang; Xinhao Xu; Shangman Li; Weiyu Feng; Mahmoud Almasri (Computers & Education: X Reality)
This paper details the design and development of an immersive and self-guided Virtual Reality training system (iSGVRTS) for learning cleanroom microfabrication operations, with a specific emphasis on the photolithography process, within a college-level semiconductor laboratory curriculum. It presents the thorough construction of the iSGVRTS environment as well as the incorporation of integrated instructional methodologies. To assess the impact of the iSGVRTS intervention, pre-and post-tests were administered to evaluate learners' performance. The implementation of iSGVRTS yielded a notable enhancement for learners in laboratory operational proficiency, evidenced by improvements in task correct rates, reduction in procedural errors, and knowledge acquisition. Moreover, post-session interviews revealed learners’ reported increased confidence, a heightened sense of presence, manageable cognitive load, and positive feedback regarding the immersive learning experience.